1998
DOI: 10.1063/1.368555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the real shape of a sample on the pinning induced magnetostriction

Abstract: The pinning induced magnetostriction in an isotropic superconductor was calculated for different sample shapes. We analyzed some special shapes for which the solution can be found analytically. The magnetostriction of a finite slab was considered. In order to determine the influence of demagnetization effects, the pinning induced magnetostriction of an infinitely long and thin strip was calculated. A simple, approximate formula can be used in particular cases to analyze the magnetostriction induced by pinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…The model proposed in ref. [1] was used by other authors for more realistic geometries [2][3][4][5][6][7][8][9]. The magnetostriction was also measured for various type-II superconductors [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The model proposed in ref. [1] was used by other authors for more realistic geometries [2][3][4][5][6][7][8][9]. The magnetostriction was also measured for various type-II superconductors [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the magnetostriction of the irradiated and unirradiated HTS ceramics may be very helpful in understanding the magnetostriction mechanism in these samples. In our previous paper [4] we reported about the magnetostriction of an order of 10 −6 at 4.2 K and 12 T in a ceramic sample of YBa 2 Cu 3 O 7−δ . The sample was next subjected to the fast neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of the well-known Bean model [3], assuming the critical current density to be independent (or at least weakly dependent) on the magnetic field, it is easy to correlate the critical current density with the width of the magnetization hysteresis loop, a similar procedure can also be applied in the case of the magnetostriction hysteresis loops. For an isotropic material and for some simple sample geometries (slab or cylinder) the width of the transverse magnetostriction hysteresis loop (∆λ trans ) can be connected with the width of the magnetization hysteresis loop (∆M ) by a simple formula [4]:…”
Section: Introductionmentioning
confidence: 99%
“…With the development of engineering applications, major efforts are directed towards improvements on mechanical performances of HTS bulks in the presence of high magnetic field. During the past years, a series of investigations were devoted to the magneto-elastic behaviors induced by flux-pinning in bulk superconductors for different sample shapes, critical state models and magnetization processes [4][5][6]. For example, Johansen studied magnetostrictive behavior during the field activation processes, and revealed that the giant irreversible magnetostriction and internal stress could often lead to fatal cracking of the HTS bulks [7].…”
Section: Introductionmentioning
confidence: 99%